Environmental policy design and the fragmentation of international markets for innovation - Nick Johnstone; Ivan Hascic (Center for Economic Studies and ifo Institute (CESifo), 2009)
It has long been argued that the implementation of market-based environmental policy instruments such as environmentally-related taxes and tradable permits is likely to lead to greater technological innovation than more direct forms of regulation such as technology-based standards. One of the principle reasons for such an assertion is that they give firms greater flexibility? to identify the optimal means of innovating to meet the given environmental objective. Thus, it can be argued that the benefits of (some) market-based instruments can also be true of well-designed performance standards. While the theoretical case for the use of flexible policy instruments is well-developed, empirical evidence remains limited. Drawing upon a database of patent applications from a cross-section of countries evidence is provided for the positive effect of flexibility? of the domestic environmental policy regime on the propensity for the inventions induced to be diffused widely in the world economy. For a given level of policy stringency, countries with more flexible environmental policies are more likely to generate innovations which are diffused widely and are more likely to benefit from innovations generated elsewhere. And while the focus of this paper is on the specific case of environmental policy, the discussion is equally applicable to aspects of product and labour market regulation which have implications for technological innovation, such as product and workplace safety.
Keywords: Q55; Q56; Q58; O31; O33; O38; 330; environmental policy; market fragmentation; innovation; technology transfer; Umweltpolitik; Flexibilität; Marktmechanismus; Wirkungsanalyse; Umwelttechnik; Innovation; Innovationsdiffusion; Technologietransfer; Welt